Peripheral neuropathy and solitary plasmacytoma. Issue 2 (February 1978) - Read, D; Warlow, C
Abstract : Three patients with peripheral neuropathy and a solitary plasmacytoma are presented, and the literature is reviewed. It is suggested that middle-aged men with an obscure progressive sensorimotor neuropathy, a raised CSF protein, and otherwise negative investigations should have a full skeletal survey since irradiation of a plasmacytoma may lead to a considerable improvement in the associated neurological disability.